Later Plantagenet and the Wars of the Roses Consorts
XXIII, 292 p. 11 illus., 9 illus. in color.
Keywords: “This impressive volume brings together the best new work on queens consort of late medieval England. A model for how to present a coherent overview of a subject as complex as these queens, a dozen scholars craft vivid and rich yet concise portraits of queens from Isabella of France to Anne Neville.” —Theresa M. Earenfight, Seattle University, USA This book examines the lives and tenures of the consorts of the Plantagenet dynasty during the later Middle Ages, encompassing two major conflicts—the Hundred Years’ War and the Wars of the Roses. The figures in this volume include well-known consorts such as the “She Wolves” Isabella of France and Margaret of Anjou, as well as queens who are often overlooked, such as Philippa of Hainault and Joan of Navarre. These innovative and authoritative biographies bring a fresh approach to the consorts of this period—challenging negative perceptions created by complex political circumstances and the narrow expectations of laterwriters, and demonstrating the breadth of possibilities in later medieval queenship. Their conclusions shed fresh light on both the politics of the day and the wider position of women in this age. This volume and its companions reveal the changing nature of English consortship from the Norman Conquest to today. Aidan Norrie is Lecturer in History and Programme Leader at the University Campus North Lincolnshire, UK, and the Managing Editor of The London Journal. Carolyn Harris is Instructor in History at the University of Toronto School of Continuing Studies, Canada, and a regular royal commentator in Canadian media. J.L. Laynesmith is Visiting Research Fellow in Medieval Studies at the University of Reading, UK. Danna R. Messer is Senior Acquisitions Editor at Arc Humanities Press, and the Executive Editorof The Encyclopedia of the Global Middle Ages. Elena Woodacre is Reader in Renaissance History at the University of Winchester, UK, Editor-in-Chief of the Royal Studies Journal, and the founder of the Royal Studies Network.